If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -10 = 4x + 11 Reorder the terms: -10 + 2x = 4x + 11 Reorder the terms: -10 + 2x = 11 + 4x Solving -10 + 2x = 11 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -10 + 2x + -4x = 11 + 4x + -4x Combine like terms: 2x + -4x = -2x -10 + -2x = 11 + 4x + -4x Combine like terms: 4x + -4x = 0 -10 + -2x = 11 + 0 -10 + -2x = 11 Add '10' to each side of the equation. -10 + 10 + -2x = 11 + 10 Combine like terms: -10 + 10 = 0 0 + -2x = 11 + 10 -2x = 11 + 10 Combine like terms: 11 + 10 = 21 -2x = 21 Divide each side by '-2'. x = -10.5 Simplifying x = -10.5
| ln(4e^2x)=3 | | n+(n+2)= | | 6X-14=-3 | | 4*(8-4x)(2x+9)(3x-1)=0 | | 4(2z-3)=20-2(2z+1) | | 7x-23=5 | | -7x+51=-x-3 | | 42-4x=6-10x | | 2(4y+3)=22 | | 3(11-t)=27 | | 5p=18 | | 9k+8k-4-2k= | | 6(6x-5)(2x+5)=0 | | 5m-3=3m+7 | | 13x+85=9x+8+15x | | -4=12y | | 2x^2+8x-169=0 | | 2z+6=7 | | 2y+6x=40 | | 10x-5y=16 | | -k-5=-129 | | -6x-36=-2x | | 5(3x+2)=-6x-11 | | 2m+3m+8= | | 2x^2+8x+169=0 | | 2ln(x+1)=4 | | x+15-33=2559 | | (x-5)*3x=0 | | 17-6x=5-10x | | 9x-38=4x+7 | | 2.25=15w | | 5m+4=34 |